Surgical spacer placement and proton radiotherapy for unresectable hepatocellular carcinoma - Komatsu, Shohei (Baishideng, 2010)
Few potentially curative treatment options exist apart from hepatic resection for patients with huge hepatocellular carcinoma (HCC). Proton radiotherapy is a promising new modality which has an inherent anti-tumor effect against HCC. However, the application of proton radiotherapy for tumors adjacent to the gastrointestinal tract is restricted because the tolerance dose of the intestine is extremely low. A novel two-step treatment was developed with surgical spacer placement and subsequent proton radiotherapy to administer proton radiotherapy with curative intent. This report presents a case of a patient with a huge unresectable HCC treated by this method who achieved disease-free survival of more than 2 years. This new strategy may potentially be an innovative and standard therapy for unresectable HCC in the near future.